2023
DOI: 10.1007/s12281-023-00464-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of COVID-19–Associated Mucormycosis

Abstract: Purpose of the Review To describe the epidemiology and risk factors for Coronavirus disease-19 (COVID-19)–associated mucormycosis (CAM) based on current published literature. Recent Findings COVID-19 is associated with an increased risk of secondary infections. Mucormycosis is an uncommon invasive fungal infection that typically affects people with immunocompromising conditions and uncontrolled diabetes. Treatment of mucormycosis is challenging and is associated with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 97 publications
0
0
0
Order By: Relevance
“…Un perfil de riesgo común identificado para la mucormicosis incluye diabetes no controlada y tratamiento con esteroides [22]. Es posible que hayan influido la desregulación inmunitaria inducida por la COVID-19, así como algunos factores de riesgo únicos y específicos de la pandemia [31]. Existen publicaciones como los señala Martin Hoenigl et al que indica que la mucormicosis asociada a COVID-19 se asocia con una alta morbilidad y mortalidad [32], diferente a nuestros resultados, donde no encontramos asociación.…”
Section: Resultsunclassified
“…Un perfil de riesgo común identificado para la mucormicosis incluye diabetes no controlada y tratamiento con esteroides [22]. Es posible que hayan influido la desregulación inmunitaria inducida por la COVID-19, así como algunos factores de riesgo únicos y específicos de la pandemia [31]. Existen publicaciones como los señala Martin Hoenigl et al que indica que la mucormicosis asociada a COVID-19 se asocia con una alta morbilidad y mortalidad [32], diferente a nuestros resultados, donde no encontramos asociación.…”
Section: Resultsunclassified
“…With the emergence of COVID-19, the number of mucormycosis infections increased drastically, particularly in India and other low-income and middle-income countries [11,12]. Common risk factors for mucormycosis are a weakened immune system, e.g., due to illness or medication, diabetes mellitus and, as in COVID-19 associated mucormycosis (CAM), primary infections [13]. Treatment recommendations for adults were published by the European Confederation of Medical Mycology (ECMM) and the Mycoses Study Group Education & Research Consortium (MSG ERC) in 2019 [14].…”
Section: Introductionmentioning
confidence: 99%
“…Mucormycosis is an opportunistic infection occurred in patients with predisposing factors leading to immunosuppressive condition. Recent meta-analyses reported that COVID-19 exposure was associated with additional risk of mucormycosis infection, mainly due to the comorbidities (e.g., diabetes, kidney disease) and the use of corticosteroid [1][2][3]. The application of corticosteroid improves the outcomes of COVID-19 patients but suppressed immune defense resulting in co-infection.…”
mentioning
confidence: 99%